Merchants of labor recruiters and international labor migration - Martin, Philip L. 1949- (Oxford, United Kingdom Oxford University Press, 2017)
"Some 10 million migrant workers cross national borders each year and, if they pay an average $1,000 to recruiters, moving workers over borders is a $10 billion a year business. Merchants of Labor examines the businesses that move low-skilled workers over national borders, asking how much they collect from migrant workers and what can be done to reduce worker-paid migration costs. Using cost data from over 3,000 workers, Merchants of Labor examines the often murky world of labor brokers, travel agents, and others who move low-skilled workers from one country to another in order to explore lower worker-paid migration costs. It explains the three core functions of labor markets-- recruitment, remuneration, and retention-- and shows how national borders increase recruitment costs. New data on what workers pay to get jobs in other countries are presented, and incentives to complement enforcement are explored as a way to induce recruiters to protect migrant workers."--
Part I: Labor Migration and Labor Markets: 1. International Labor Migration -- 2. Labor Markets and Migration.

Part II: What do Workers Pay?: 3. Migration Costs in Destinations -- 4 Migration Costs of Returning Workers.

Part III: Regulating Recruitment: 5. The Recruiting Business -- 6. Regulating Recruiters -- 7. Recruiter Incentives and Alternatives -- 8. Employers, Recruiters, and Workers.
Includes bibliographical references (pages 189-200) and index.
Keywords: Foreign workers; Manpower policy; Emigration and immigration -- Economic aspects; Foreign workers -- Civil rights